A dynamic leaf gas‐exchange strategy is conserved in woody plants under changing ambient CO2: evidence from carbon isotope discrimination in paleo and CO2 enrichment studies. (4th January 2016) - Voelker, Steven L.; Brooks, J. Renée; Meinzer, Frederick C.; Anderson, Rebecca; Bader, Martin K.‐F.; Battipaglia, Giovanna; Becklin, Katie M.; Beerling, David; Bert, Didier; Betancourt, Julio L.; Dawson, Todd E.; Domec, Jean‐Christophe; et al.
Abstract: Rising atmospheric [CO2 ], c a, is expected to affect stomatal regulation of leaf gas‐exchange of woody plants, thus influencing energy fluxes as well as carbon (C), water, and nutrient cycling of forests. Researchers have proposed various strategies for stomatal regulation of leaf gas‐exchange that include maintaining a constant leaf internal [CO2 ], c i, a constant drawdown in CO2 ( c a − c i ), and a constant c i / c a . These strategies can result in drastically different consequences for leaf gas‐exchange. The accuracy of Earth systems models depends in part on assumptions about generalizable patterns in leaf gas‐exchange responses to varying c a . The concept of optimal stomatal behavior, exemplified by woody plants shifting along a continuum of these strategies, provides a unifying framework for understanding leaf gas‐exchange responses to c a . To assess leaf gas‐exchange regulation strategies, we analyzed patterns in c i inferred from studies reporting C stable isotope ratios (δ 13 C) or photosynthetic discrimination (∆) in woody angiosperms and gymnosperms that grew across a range of c a spanning at least 100 ppm. Our results suggest that much of the c a ‐induced changes in c i / c a occurred across c a spanning 200 to 400 ppm. These patterns imply that c a − c i will eventually approach a constant level at high c a because assimilation rates will reach a maximum and stomatal conductance of each species should be constrained to some minimum level. These analyses are not consistent with canalization toward any single strategy, particularly maintaining a constant c i . Rather, the results are consistent with the existence of a broadly conserved pattern of stomatal optimization in woody angiosperms and gymnosperms. This results in trees being profligate water users at low c a, when additional water loss is small for each unit of C gain, and increasingly water‐conservative at high c a, when photosystems are saturated and water loss is large for each unit C gain.